Technological Developments and Change in Armed Forces Recruitment Systems - ÇOKGEZEN, MURAT (My University, 2024)
The impact of technological changes in military technology on warfare, military organizations, and peace has been investigated by a number of researchers but only very few explicitly refer to the effects of technological changes on the military recruitment systems. With the aim of filling this gap, this study, based on previous studies examining war history and military technology, hypothesizes that long-running trends in military recruitment systems, from professional armies to conscription or the other way round, can be explained by the changes in military technology. We assert that as military technology changed, so too did the skills required for those technologies, and, in turn, those need by the recruitment system and therefore the system itself. Although changes in military technology may explain the long-term cycles, one should keep in mind that we need the other determinants discussed in the literature to understand why different countries switched from one military recruitment system to another at different times throughout the cycle. Further studies, simultaneously taking into account both the impact of the changes in military technology as well as other variables, would improve our understanding of the determinants of the changes in military recruitment systems.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; TARİH; Arts & Humanities (AHCI); ARTS & HUMANITIES; HISTORY; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; conscription; Military recruitment; military technology; professionalism